(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Different genetic and environmental factors appear to be involved in the pathogenesis of classical Hodgkin’s lymphoma (HL) and among them is Epstein Barr virus. Objective:To evaluate the immunohistochemical expression of the Latent Membrane Protein-1 of Epstein-Barr virus and Bcl-2 in Classical Hodgkin Lymphoma and to correlates this expression with some clinicopathological parameters and finally to find if there is any relation between LMP-1 and Bcl-2 in classical Hodgkin’s lymphoma. Method:Retrospective study of fifty paraffin-embedded blocks of lymph nodes biopsies from patients diagnosed as Classical Hodgkin’s Lymphoma. Three representative sections were prepared for each case. The first stained with H&E and the other two sections stained immunohistochemically for LMP-1 and Bcl-2 . Results: Immunohistochemical expression of LMP-1 and Bcl-2 was detected in 90% and 66% of Hodgkin’s lymphoma cases and in 60% and 80% of control subjects, respectively. The patients (9/50) who were less than 16 years were positive for LMP-1 antigen. 21/45 (46.6%) of positive cases for LMP-1 & 14/33 (42%) of positive cases for Bcl-2 were of mixed cellularity subtype. Intensity of LMP-1 but not Bcl-2 expression was significantly high in mixed cellularity compared to other subtypes. No statistically significant relation between LMP-1 and Bcl-2 expression in HRS cells of Hodgkin’s lymphoma cases. Conclusion:The high prevalence and high expression of LMP-1 confirms the association of the virus with HL. Although Bcl-2 is highly expressed in HL, the two markers were not related to each other. Keywords:Classical Hodgkin’s Lymphoma, Epstein Barr virus, Immunohistochemistry,Epstein Barr virus latent membrane protein-1, Bcl-2.